Beyond species counts for assessing, valuing, and conserving biodiversity: response to Wallach et al. 2019 - Ninon F. V. Meyer; Niko Balkenhol; Trishna Dutta; Maarten Hofman; Jean‐Yves Meyer; Euan G. Ritchie; Charlotte Alley; Chad Beranek; Cassandra K. Bugir; Alex Callen; Simon Clulow; Michael V. Cove; et al. (Conservation Biology, 2021)
Article impact statement : Combining native and non‐native species to evaluate biodiversity is overly simplistic and may undermine the conservation of ecosystems.

Reproductive and Physiological Effects of Environmental Contaminants in Fish-Eating Birds of the Great Lakes: A Review of Historical Trends - Keith A. Grasman; Patrick F. Scanlon; Glen A. Fox (Environmental Monitoring and Assessment, 1998)

Sublethal effects of cadmium ingestion on mallard ducks - Richard T. Di Giulio; Patrick F. Scanlon (Archives of Environmental Contamination and Toxicology, 1984)

Tissue lead concentrations and blood characteristics of mourning doves from Southwestern Virginia - Ronald J. Kendall; Patrick F. Scanlon (Archives of Environmental Contamination and Toxicology, 1982)

Tissue lead concentrations and blood characteristics of rock doves from an urban setting in Virginia - Ronald J. Kendall; Patrick F. Scanlon (Archives of Environmental Contamination and Toxicology, 1982)

Toxicology of ingested lead shot in ringed turtle doves - Ronald J. Kendall; Patrick F. Scanlon; Richard T. Di Giulio (Archives of Environmental Contamination and Toxicology, 1982)